Juridical Study Of Planning Murder Cases (Study Decision Number 91PID.B2022PN KRW) - Pahlepi, Hendra; Amaliya, Lia; Dewi, Sartika (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Crime is someone's behavior that violates positive law or law that has been legitimized in force in a country. In this case premeditated murder is the crime of taking the life of another human being, or killing, after planning the time or method, with the aim of ensuring the success of the murder. The problem is how the juridical aspects relate to the handling of premeditated murder cases and how the judge considers them when deciding on murder cases in Decision Number 91/Pid.B/2022/Pn.Krw. Qualitative Research Method using the Normative Juridical approach method. The results of the research are the Juridical Aspects of the Elements of the Crime of Premeditated Murder, which are stated in article 340 of the Criminal Code: "Anyone who intentionally and with premeditation takes the life of another person, is threatened with premeditated murder (moord), with the death penalty or imprisonment life imprisonment or a maximum imprisonment of twenty years" namely 1) Elements of each person; 2) Elements on purpose; 3) Elements are planned in advance; 4) The element of eliminating other people's souls. The Judge's Considerations in Deciding on a Murder Crime Case in Decision Number 91/Pid.B/2022/Pn.Krw, namely as in Article 183 of the Criminal Procedure Code that the considerations prepared include the facts and circumstances along with evidence of at least two pieces of evidence obtained from the examination at trial which is the basis for determining the defendant's guilt. In accordance with the facts at trial and it has been concluded that the defendants have been legally and convincingly proven guilty of committing the crime of participating in murder with premeditation as stated in the first indictment of the public prosecutor. And based on the considerations above, all conditions of punishment have been fulfilled, both the objective conditions of a criminal act and the subjective conditions of criminal responsibility. In this way, the Panel of Judges did not find any justification or excuse for the defendant for the criminal acts he committed, therefore the defendants must be punished according to their actions.